System Programming in Loaders - *, Komal; Hazrati, Karuna; Mittal, Priyanka (IJRDO -Journal of Computer Science Engineering, 2015)
Linkers and loaders have been part of the software toolkit almost as long as there have been computers, since they are the critical tools that permit programs to be built from modules rather than as one big monolith. Linking and Loading, provides a short historical overview of the linking process, and discusses the stages of the linking process to execute an object program, we needs Relocation, Linking, Loading and Allocation